Analisis Implementasi E-Procurement Terhadap Kinerja Pada Pengadaan Barang Dan Jasa Di Pemerintah Daerah - Rumsiana, Eka Yulia Anik (Peneliti.net, 2024)
The Tender Demand with Electronic site is Important for Regional Government and its official as therefore could sustain advance stabilization within the region but its very difficult to operate without media to sustain the matters. The Beneficences about the application of the Electronic Order, beside can minimize the time, it also can also a vested interest for supplier participates towards Public Utilization because it can reduce fraud because The Goods are supervised electronically as it avoid direct transactions between Supplier and Customers. But in that way there is a fraud as a way of doing against law, the crimes is an indication against Nation Will to create stability governmental situation. The State Institution observes line of ordering offer and Good Purchase ordered by Electronic fraud can reduce properly, the conclusion of research is to create a design a fraud case and how to minimize it with some methods..